Efficient and Selective Hydrogen Generation from Bioethanol using Ruthenium Pincer‐type Complexes. Issue 9 (1st August 2014) - Sponholz, Peter; Mellmann, Dörthe; Cordes, Christoph; Alsabeh, Pamela G.; Li, Bin; Li, Yang; Nielsen, Martin; Junge, Henrik; Dixneuf, Pierre; Beller, Matthias
Abstract Catalytic generation of hydrogen from aqueous ethanol solution proceeds in the presence of pincer‐type transition metal catalysts. Optimal results are obtained applying a [Ru(H)(Cl)(CO)(iPr2PEtN(H)EtPiPr2)] complex (catalyst TON 80 000) in the presence of water and base. This dehydrogenation reaction provides up to 70 % acetic acid in a selective manner. For the first time, it is shown that bioethanol obtained from fermentation processes can be used directly in this protocol without the need for water removal. The produced hydrogen can be directly utilized in proton exchange membrane (PEM) fuel cells, since very low amounts of CO are formed.